Heaven official's blessing = Tian guan ci fu. 6 - Moxiangtongxiu (Seven Seas, 2023)
Body in abyss, heart in paradise. White No-Face, Xie Lian's greatest fear and most hated enemy, has arrived...or so it seems. While the ghost with the half-crying, half-smiling mask is somewhere nearby, the creature is elusive as always, taunting Xie Lian from just out of reach and promising the total destruction of everything he holds dear. As Xie Lian confronts the trauma of his last encounter with the terrifying ghost, Hua Cheng will do anything in his power to protect him. But White No-Face's identity and purpose are not the only mysteries to unravel, as Hua Cheng also has a history in the labyrinthine tunnels beneath Mount Tonglu. Will Xie Lian finally discover the full connection they share--and learn the true depths of Hua Cheng's devotion?